Analytic Network Process on Financial Access of the Small and Medium Enterprise in Sharia Banking in Tasikmalaya City - Suryanto, Asep; Nasution, Fatimah Zahra (International Journal of Nusantara Islam, 2015)
Small and Medium Enterprise (SME) has a significant role in national economic development. The increase of Small and Medium Enterprise is followed by the rise in employment absorbment and equity in income distribution. The capital constraint and the impedance of banking financial access have become the main problem to the Small and Medium entrepreneurs. The objectives of this research: 1) To identify the main factors as problems of Small and Medium Enterprises in having access to the financial institutions.2) To find the solutions of the research problems. This research used qualitative approach i.e. Analytic Network Process (ANP). For applying this method, it is expected to help the researchers in making measurement and sinthesis of some factors regarding the topic analyzed as well as finding the solution for problems faced by the SMEs. Data used in this research is primary data collected from questionaires and indepth interview with experts, practitioners, SMEs and regulators which then analyzed by structuringthe hierarchi into homogen clusters of the SMEs problems and solutions, measuring into ratio scale and building sinthesis. As the result, it becomes clear what factors impeding the financial access of the SMEs to banks. The results of this research shows that the difficulties of SMEs in accessing financial support in islamic financial institutions are internal problems of islamic banking i.e. 1) lack of financial assistance given to the SMEs, 2) the functions of islamic banking as business partners for SMEs is not optimal. Whereas the external problems in the SMEs is the disability in meeting the financial requirements asked by islamic banking that is collateral and business history. The solutions are: 1) internal solution; islamic banking should give business mentoring to SMEs that have received financial supports to minimalize the bad credits level. 2) external solution; the government should socialize islamic financial mechanism to SMEs as part of education efforts.